PENANGANAN TINDAK PIDANA PENCABULAN DI INDONESIA KAITANNYA DENGAN CYBER - H. M. Yusuf DM; Qodri, Rahmat Tul; Rizki, Ridwan; Nduru, Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
Basically, the regulation of sanctions for child molestation has been widely found in the Law and Government Regulations, this can be seen in the Criminal Code (KUHP). In reality, the implementation of these regulations can still be said to be ineffective. This can be seen from the increasing number of child molestation crimes that have occurred in Indonesia. The research that will be conducted by the author is normative, namely research based on applicable legal principles. The results of the research in this study are the handling of child molestation crimes in Indonesia in relation to cyber is a form of implementation itself, meaning that all forms of laws and regulations governing child protection used in law enforcement itself are a form of implementation. In general, child molestation laws can be seen in several stages, namely the Investigation and Investigation Process, the Child Examination Process, and the Trial Process.